Motivational Optimism and Short-Term Investment Efficiency - Li, Meng; Markov, Stanimir; Shu, Susan (The Accounting Review, 2023)
ABSTRACT We explore whether managers’ strong desire for good performance distorts their expectations and, consequently, corporate investment efficiency. We find that managers overweight favorable information and underweight unfavorable information, resulting in optimistic earnings guidance. We construct an ex ante measure of optimism and show that greater optimism is associated with a lower inventory investment efficiency: Managers overinvest in inventory, resulting in lower inventory turnover and increased incidence and severity of inventory writedowns. We also find motivational optimism influences firms’ financial reporting and is associated with an increased incidence of financial misreporting. Our results are consistent with the psychology theory of motivated reasoning, which emphasizes the distortive effects of preferences on beliefs and judgments. JEL Classifications: M41; D91; G41; G31.